Research and implementation of safety authentication technology in Internet of vehicles - Manzhu WANG; Ziqi LI; Yifei CHEN; Gaofeng HONG; Wei SU (物联网学报)
Nowadays, safety certification technology for Internet of vehicles (IoV) cannot well defend the various attacks, and there are also many shortcomings when considering the balance between safety and performance.Based on the in-depth analysis of the research status and security threats for IoV, a hierarchical vehicle-to-vehicle (V2V) safety authentication scheme was proposed.Furthermore, an L-type safety authentication scheme which based on more than one trusted third parties was proposed.Aimed at ensuring the information safety of the communication process and preventing the communication data from being stolen, the schemes were more suitable to IoV.